Coexistence of directional and non-directional technologies in 6G wireless dense networks - Abdalla, Iman (2021)
Dense networks are characterized by the prevalence of wireless access points (APs) in close proximity to a population of user devices on a similar scale. By increasing AP density, the aggregate data consumption of a system can be dramatically increased.